Synthesis of the WC and Mo₂C Carbides by Mechanical Alloying of Metal Powder and Carbon Nanotubes - Nakonechna, O.; Dashevskyi, M.; Belyavina, N. (Металлофизика и новейшие технологии, 2018)
Nanoscale WC and Mo₂C carbides are synthesized from the elemental metal powder (with particle size of about 40 μμm; purity is not less than 99.6% wt.) and the carbon nanotubes (CNTs, with average diameter of 10–20 nm) by mechanical alloying in a high-energy planetary ball mill for the first time.